Nutritional status of underfive children of less privileged families in Medan - Indra B. Hutagalung; Bangun Lubis; Ridwanto Ridwanto; Hakimi Hakimi; Endang D. Hamid (Paediatrica Indonesiana, 2001)
A cross sectional study was done on 94 under five children taken from Keluarga Pra-sejahtera (pre-prosperous family=-pre-PF) and Keluarga Sejahtera Tahap-1 (prosperous family phase-I=PF-I) in the East Medan subdistrict, municipality of Medan in period of August 1995 up to February 1996. The aim of the study was to measure nutritional status of under five children in both groups. There were 94 under five children in group of ore-PF and 94 under five children in group of PF-l. It was found that the nutritional status of both groups was significantly different. Significant difference was also noted when they were classified according to father's occupational status and father's education level. However when they were grouped according to maternal education, number of children in the family, and occurrence of disease in the previous month no significant difference was detected.